Solve for x
![3{x}^{2} - 6x + 2 = 0 3{x}^{2} - 6x + 2 = 0](https://tex.z-dn.net/?f=+3%7Bx%7D%5E%7B2%7D+++-+6x+%2B+2+%3D+0)
Answers
Answered by
5
Answer:
Step-by-step explanation:
Mark as Brainlies
Attachments:
![](https://hi-static.z-dn.net/files/d23/56c2dbb09b1a13dcc76562d40d867fb3.jpg)
Answered by
7
Answer:
Step-by-step explanation:
Given:
To solve this problem, first you have to find the value of x from left to right. Isolate by the x on one side of the equation.
Solutions:
First, used quadratic equation formula.
A=3
B=(-6)
C=2
Solve.
Next, multiply the numbers from left to right.
Factor it out.
Common factor of 2.
Solve.
Therefore, the correct answer is x=3+√3/3, x=3-√3/3, x=1.57, and x=0.42.
Similar questions